2012
DOI: 10.3233/wor-2012-0322-1346
|View full text |Cite
|
Sign up to set email alerts
|

Openability of soft drinks PET packagings

Abstract: Studies on packaging accessibility are still incipient in Brazil. Many of these packagings can represent a challenge to users, whether due to non-informative labels, tricky tabs or seals, or even those that need strength to open. This paper brings a simple test to determine the necessary torque force to open PET bottles, and to predict the amount of users that could not open it. The findings suggest that a considerable amount of users could not open it or would have some difficulties to exert the necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Gofman et al, 38 Yiangkamolsing et al, 135 de la Fuente et al, 166 and Langley et al 167 The packaging design process should be structured to link between users' requirements and design parameters. Silva et al, 168 Yoxall et al, 169,172 Blakey et al, 170 and Chihara et al 171 Opening difficulties can be addressed either by introducing opening-aiding tools or applying design efforts.…”
Section: Packaging Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Gofman et al, 38 Yiangkamolsing et al, 135 de la Fuente et al, 166 and Langley et al 167 The packaging design process should be structured to link between users' requirements and design parameters. Silva et al, 168 Yoxall et al, 169,172 Blakey et al, 170 and Chihara et al 171 Opening difficulties can be addressed either by introducing opening-aiding tools or applying design efforts.…”
Section: Packaging Designmentioning
confidence: 99%
“…In general, a package can be difficult to open because of the complexity of the opening system, useless instruction, or the force required. 168 Identifying such factors can help designers to produce efficient packaging designs while eliminating opening difficulties. For example, predicting the most preferred grip style while opening peelable packages gives designers valuable information and helps them in designing a package considering users' behavior and preferences.…”
Section: Packaging Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have already shown that although the opening mechanism of the packages is familiar, elderly consumers might not be successful in opening the packaging just because they are unable to exert sufficient force. 9,17,27,37 Packaging types with torque usually involve both hands, the non-dominant hand that holds the packaging and provides the counter pressure and the active hand that simultaneously performs a rotating movement. 24 Apart from age, gender, grip strength and wrist strength, the diameter of the closure and the coefficient of friction between the hand and the bottle closure are factors that affect the ability to open a bottle.…”
Section: Comparison Of the Quantitative Force Measurements With The Qmentioning
confidence: 99%
“…There have been numerous previous studies examining the openability of packaging across various disciplines, from the study of Rholes et al ., the Department of Trade and Industry, Voorbij and Steenbekkers and Yoxall et al . and more recently of Yoxall and Janson, Su et al ., Kuo et al ., Chihara and Yamazaki, Silva et al . and Bix .…”
Section: Introductionmentioning
confidence: 99%